Lectin-like oxidized low-density lipoprotein receptor 1 mediates phagocytosis of aged/apoptotic cells in endothelial cells - Oka, Kozo (The National Academy of Sciences, 1998)
Recognition of the exposure of phosphatidylserine (PS) on the outer surface of plasma membrane has been implicated in the phagocytosis of aged/apoptotic cells. Because oxidized low-density lipoprotein (OxLDL) has been reported to block the phagocytosis, here we examined whether lectin-like OxLDL receptor 1 (LOX-1), the OxLDL receptor in endothelial cells, mediates phagocytosis of aged/apoptotic cells by endothelial cells. Cultured bovine aortic endothelial cells (BAE) and Chinese hamster ovary (CHO) cells expressing bovine LOX-1 (BLOX-1-CHO), but not wild-type CHO-K1 cells, bound aged red blood cells (RBC) and apoptotic cells, which were further phagocytosed. The binding of aged RBC and the phagocytosis of apoptotic cells were inhibited by OxLDL, acetyl LDL, and other LOX-1 ligands in both BAE and BLOX-1-CHO. mAb against LOX-1 blocked the binding of aged RBC to BAE, suggesting a role for LOX-1 in the recognition of aged cells. The recombinant soluble LOX-1 inhibited the interactions of aged/apoptotic cells with both BLOX-1-CHO and BAE and distinguished aged RBC from native RBC and apoptotic cells from native cells. PS liposome inhibited these LOX-1-mediated interactions with aged/apoptotic cells, suggesting LOX-1 recognizes PS of the apoptotic cells. PS exposed on the surface of apoptotic cells is known to be procoagulant. Accordingly, increased OxLDL may be one of the reasons for enhanced coagulation in atherosclerosis, inhibiting the removal of apoptotic cells.